Outcome of Transfer Flexor Carpi Ulnaris And Plmaris Longus Tendons for Hand Deformity in Persistance Radial Nerve Palsy - Shoja’a, Abdullrakeeb; Naeem, Abdullah Y.; Abdulla , Hefzulla M.; Albhloly, Saeed (Thamar University Journal of Natural & Applied Sciences, 2024)
Objective; the aim of our study is to evaluate the functional outcome of transfer flexor carpi ulnaris and palmaris longus for patients with persistence radial nerve palsy by minimal tendon transfer technique.Methods; The study included 10 patients 8 male and two female, mean age 25 years, range from 20 to 30 years. They underwent transfer of flexor carpi ulnaris (FCU) and palmaris longus (PL) tendon for patient with persistence radial nerve palsy, the duration of outcome of tendon transfer after radial nerve injury evaluated after one year. Clinical evaluation include wrist joint range of movement by Geniometry and compared with the contralateral normal side.Results; The average ranges of wrist movements were as the follows: the mean wrist flexion was 52⁰(range 46⁰–56⁰), the mean wrist extension was 34⁰(range 30–38), radial deviation 18⁰(range 16⁰–20⁰) and ulnar deviation 21⁰ (range 18–23). The mean extension of the fingers in wrist extension was 7⁰(range 5⁰–10⁰) and in wrist neutral position was 12⁰(range 9⁰–16⁰). The mean abduction of the thumb was 38⁰(range 35⁰–44⁰). In comparison to the measure of joints in the contralateral normal hand, the final extension of the wrist was less, but extension of the fingers and MCP joints was similar to that of the normal hand. All of the patients in our study were able to extend their fingers with the wrist in the neutral position. Thumb abduction and extension was sufficient to deal with daily activities and, even, heavy jobs in most of the patients.  Postoperative follow up of the patients was ranged (12–24) months. After 45 days, 8o% of the patients were able to do the normal non heavy daily work. In 20% of cases recovery was not progressing satisfactorily at 5 weeks. These were referred to physiotherapy for a planned exercise program, which the two patients improved their movements.Conclusion; The purpose of this study was to evaluate function of the hand   after   transfer   of   the   FCU   to   EDC   and  PL to EPL, with persistence high nerve injuries. The FCU & PL tendons transfer has some advantages over the other techniques, short duration of operation time, no morbidity, improve range of motion of hand and less surgical scares. It is a viable option to restore hand function and strength following radial nerve injuries.